Preliminary Study of Common House Gecko (Cosymbotus platyurus) Density in Java Island - Suwatik Suwatik; Nenden Sri Wahyuni; Santi Mulyawati; Mulik Siti Nur Rohmah; Rr. Indira Dewi Anggraeni; Raflen Ari Gerungan; Diki Diki (International Journal of Research in Community Services, 2021)
Common house gecko (Cosymbotus platyurus) is the most abundant house gecko species in Indonesia. The geckos live in home yard, garden, and in homes. It is part of food chain in its habitat, as its preys include cockroaches, flies, and termites. Previous studies found that this gecko are not found in mountainous area in West Java. In this study, the researchers observe population density of common house geckos in various types of habitats (houses and parks) with their home territory. The methods used were direct survey methods followed by literature study. The study is conducted in Java island (Jakarta, Tangerang, Bandung, Bogor, Sleman). Preliminary result of this study is house geckos are very active at night, because of the effect of light produced by lights that attract the attention of insects, gecko food.